PKU BAGI GURU BK SMK KOTA MAGELANG UNTUK MENINGKATKAN LAYANAN DAN KINERJA BK MELALUI ANALISIS SOSIOMETRI-SOSIOGRAM - Hijrah Eko Putro (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
University partnership program aims to:(1) improve the performance and the quality of the guidance and counseling teacher in the school environment; (2) increase of innovations in managing the administration of guidance and based sociometri – sociogram. The devotion is carried out in the laboratory of instrumentation faculty of teacher training and educational science of University of Muhammadiyah Magelang, on 19 February 2018. Trainees are guidance and counselling teacher of vocational secondary school in Magelang city. Based on the result of the University partnership can be concluded this activity can improve the understanding and skill in the use of analysis sociometri–sociogram.